Effect of extended cefquinome treatment on clinical persistence or recurrence of environmental clinical mastitis - Swinkels, J.M.; Lam, T.J.G.M.; Green, Martin J.; Bradley, Andrew J. (Elsevier, 2013)
The effectiveness of antibiotic treatment of clinical mastitis (CM) is classically evaluated using bacteriological cure, which provides a concise and objective way of assessing efficacy but does not reflect the situation in the field where persistence or recurrence of clinical signs lead to perceived treatment failure. If clinical signs persist or recur, intramammary (IMM) treatment is often extended or supplemented with parenteral therapy in the expectation of a more efficient elimination of clinical signs or a lower probability of recurrence.